CORPORATE SOCIAL RESPONCIBILITY DIPENGARUHI OLEH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE - Anisaul Hasanah; Imtiyaz Farras Mufidah (Fakultas Ekonomi Universitas Kadiri, 2023)
This study aims to determine and analyze corporate social responcibility is influenced by company size, profitability, and leverage in Food and Beverages companies listed on the Indonesia Stock Exchange (IDX) during the period 2016 – 2020. The results of this study are expected to be used by companies as material evaluation in order to increase the disclosure of Corporate Social Responsibility. Research method : This study uses a quantitative approach. The method used is the method of multiple linear regression analysis, by testing classical assumptions, testing hypotheses and coefficients of determination. The population of this study were 30 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2016 – 2020. Based on the purposive sampling method, a sample of 11 companies was obtained. The data analysis technique used in this research is multiple linear regression. Findings : The results obtained partially, Corporate Social Responsibility has a significant effect on Firm Size, Corporate Social Responsibility has a significant effect on Profitability,and Corporate Social Responsibility has no and no significant effect on Leverage. Meanwhile, simultaneously, Corporate Social Responsibility have a significant effect on Company Size, Profitability, and Leverage.